2019
DOI: 10.1155/2019/9026890
|View full text |Cite
|
Sign up to set email alerts
|

Do Upper and Lower Camptocormias Affect Gait and Postural Control in Patients with Parkinson’s Disease? An Observational Cross-Sectional Study

Abstract: Gait impairments and camptocormia (CC) are common and debilitating in patients with Parkinson’s disease (PD). Two types of CC affect patients with PD, but no studies investigated their relative contribution in worsening gait and postural control. Therefore, we investigated spatiotemporal gait parameters, gait variability, and asymmetry and postural control in PD patients (Hoehn & Yahr ≤4) with upper CC and lower CC and patients without CC. This observational cross-sectional study involving patients with PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Despite the different criteria employed, greater disability is noted in patients with CC, PS, and AC than in those without severe postural abnormalities (1). Moreover, patients with lower CC seem to have more severe gait and postural control impairment than those with upper CC and without CC (26). Our data show that the severity of trunk bending cannot fully explain impairments.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite the different criteria employed, greater disability is noted in patients with CC, PS, and AC than in those without severe postural abnormalities (1). Moreover, patients with lower CC seem to have more severe gait and postural control impairment than those with upper CC and without CC (26). Our data show that the severity of trunk bending cannot fully explain impairments.…”
Section: Discussionmentioning
confidence: 64%
“…However, we hypothesize that trunk asymmetry related to LTB may reduce trunk mobility more than FTB, leading to a greater impairment in motor functions, and intrinsic gender differences of the anatomy of the spine (24) may be a predisposing factor, along with subclinical osteoporosis for which the frequency in women is more than double that in men (25). PD-associated postural abnormalities have attracted increasing attention from clinicians and researchers since they were recognized as a frequent and disabling complication of PD (1,(3)(4)(5)(6)26). Most studies on severe forward and lateral trunk flexion (i.e., CC, PS, and AC) to date have applied arbitrary and often diverse diagnostic criteria (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gait function in PD patients with Pisa syndrome [16][17][18], which is a severe lateral-trunk-exion (LTF) posture, did not differ from that of patients without Pisa syndrome or age-matched healthy controls [19]. Notably, previous studies reporting that the type of postural abnormality affected gait function [15][16][17][18][19] did not assess sex differences; the data of subjects of both sexes were pooled. Thus, to date, sex differences in the effect of posture on gait function in PD patients have yet to be clari ed.…”
Section: Introductionmentioning
confidence: 94%
“…The in uence of posture on gait function in PD patients has also been investigated. Geroin [15] reported that PD patients with lower camptocormia had signi cantly lower gait speed, shorter stride length, and lower stride velocity than PD patients with upper camptocormia or no camptocormia; thus, lower camptocormia is associated with more severe gait and postural-control impairments. In contrast, gait function in PD patients with Pisa syndrome [16][17][18], which is a severe lateral-trunk-exion (LTF) posture, did not differ from that of patients without Pisa syndrome or age-matched healthy controls [19].…”
Section: Introductionmentioning
confidence: 99%
“…They may occur isolated or combined at different stages of disease [5]. Postural abnormalities have a multifactorial pathophysiology [1][2][3] and are associated with higher disability because they increase the risk of falls [5,6], cause back pain and reduce mobility [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%